Pelatihan Sadari Dan Pemeriksaan IVA Sebagai Upaya Deteksi Dini Kanker Di Wilayah Perdesaan: Studi Kasus Di Desa Tanjung Anom - Rustianna Tumanggor; Theresia Anggriani H; Elshadddai Tabitha Siadari; Dita Togatorop; Dina Eudia Meha (Sevaka : Hasil Kegiatan Layanan Masyarakat, 2025)
Breast cancer and cervical cancer are two leading causes of death among Indonesian women, yet they are preventable through early detection. Tanjung Anom Village in Pancur Batu Subdistrict is a rural area with low health literacy, particularly regarding cancer screening. This community service aimed to improve women's knowledge and awareness through SADARI (Breast Self-Examination) training and IVA (Visual Inspection with Acetic Acid) examination. A community-based participatory approach was applied, involving health cadres, village leaders, and women of reproductive age as key participants. The results showed a significant increase in participants’ knowledge scores, from an average of 52.4 to 76.2 after the intervention. A total of 48 women voluntarily underwent the IVA test, and a Women's Health Working Group was established to sustain ongoing education. The emergence of local leaders and collective awareness reflects a successful health-based social transformation. This program has proven effective and can be replicated in other rural settings.